MANAGEMENT MODEL DEVELOPMENT OF TEACHING FACTORY â€œPROCOM CAKEPâ€ IN THE FIELD OF ENGINEERING TECHNOLOGY (Universitas Negeri Semarang, 2014)
The management model development of Teaching Factory Procom Cakep (Production competency of a professional would-be employer) in Engineering and Technology field is a management concept which combines Production-based Training ( PBT ) learning and Competency-based Training (CBT) in the real situation, so that at minimum, the process of achieving graduatesâ€™ competency can meet the industrial world working standards. Finding and developing TEFA Procom Cakep management model in Engineering and Technology have been done through model validation with Research and Development approach. Teaching factory Procom Cakep management model orientates on business concept and production in vocational education in line with relevan skills and competences. In order to achieve the research purpose, Research and Development approach, preliminary studies, model design development, experiment, and validation have been carried out. Preliminary phase was planned to have these following steps; literary study, field study, factual field description and analysis. After this step, the model group is guided by current group to develop and implement TEFA Procom Cakep management model in Engineering and Technology. The data analysis in this research includes preliminary study, finding facts about the applied productive learning program which is reported in a data collection, and then interpreted qualitatively. The analysis of design Process and development is carried out in peer-group and expert judgment. The result of the experiment and induction is delivered in data and the applicability is analyzed in descriptive qualitative. The developed Teaching Factory management model can be applied in the executors of Procom Cakep management model in Engineering and Technology (Principal, teachers, public relation and industry partner.